STRATEGI KOMUNIKASI DIGITAL DALAM MENINGKATKAN KESADARAN VAKSINASI DI KALANGAN REMAJA - Hotmaria Hertawaty Sijabat (JOURNAL OF COMMUNITY DEDICATION, 2024)
This study analyses the impact of digital communication strategies in raising vaccination awareness among adolescents. In the midst of a global pandemic situation, the importance of obtaining accurate information about vaccination is increasingly crucial, especially for adolescent groups who are often the target of misinformation. The results showed that an interactive and participatory digital communication strategy successfully increased vaccination awareness and acceptance among adolescents. Through a direct and transparent communication approach, adolescents are able to access valid information and participate in constructive discussions about vaccination. Thus, digital communication strategies are an essential tool in efforts to increase vaccination awareness and acceptance among this age group.